Bruton tyrosine kinase inhibitor-related atrial fibrillation and its implications in the treatment of B-cell lymphoma - Du, Jun; Chen, Ze-Yu; Gu, Xiao-Ran; Wang, Ting; Huang, Zou-Fang (Frontiers in Cardiovascular Medicine, 2024)
Adverse events of atrial fibrillation (AF) have been commonly reported in lymphoma patients in treating Bruton's tyrosine kinase inhibitors (BTKi). The incidence rate of AF can vary depending on the specific types of BTKi and the patient population.Totally 42 published studies have revealed that the overall incidence rate of AF is 5% (95% CI 4%-7%). By performing a subtype single-rate analysis, the secondgeneration BTKi shows a lower AF incidence rate and lower cardiovascular toxicity.In the subtype single-rate analysis, we conclude the different AF incidence rates of Ibrutinib (10%, 95% CI 7%-13%), Acalabrutinib (4%, 95% CI 1%-6%), Orelabrutinib (0%, 95% CI 0%-1%), and Zanubrutinib (0%, 95% CI 0%-1%). The comprehensive analysis of AF inspires us to better predict and manage AF and other cardiovascular events in treating lymphoma. Meticulous evaluation, collaboration between cardiologists and hematologists, and discovery of new biomarkers are essential for its management.